A titanium ion-selective membrane electrode sensor - Kassim, Anuar; Rezayi, Majid; Ahmadzadeh, Saeid; Yusof, Noor Azah (2011)
A titanium (III) ion-selective membrane electrode sensor including a tris(2-pyridyl) methylamine ionophore, potassium tetrakis (4-chlorophenyl) borate additive, di-n-octyl phthalate plasticizer, poly(vinyl chloride) polymeric membrane and a solid body.